Analisis SWOT Produk Aroma Care untuk Menentukan Strategi Bersaing pada PT Aroma Wangi Indonesia - Dzikri, M. Fazri; Tiris Sudrartono (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
The purpose of this research is to examine PT. Aroma Wangi Indonesia's Aroma Care product using a SWOT analysis in order to identify competing tactics. Information was gathered from primary sources, such as interviews with business owners and workers, and secondary sources, such as marketing and operational strategy documents, using descriptive and qualitative methodologies. The research shows that the company's strengths include its marketing efforts, new goods made from natural components, and efficient manufacturing procedures. Threatening obstacles include, but are not limited to, severe industry rivalry and uncertain economic circumstances. The firm may take advantage of opportunities to grow, such creating new technology and entering the Bandung city market. In order to stay competitive, this research suggests a number of strategic moves, such as expanding manufacturing capabilities, diversifying raw material sources, and putting more effort into product innovation. Better methods to assist the long-term success of PT. Aroma Wangi Indonesia may be developed with the use of this study's results. Strengthening its market position and achieving sustainable development may be achieved by adopting strategic initiatives like extending product marketing, producing novel goods, and capturing possibilities like new technologies and market expansion in prospective regions of Bandung city.